FourFold Asthma Study (FAST): a study protocol for a randomised controlled trial evaluating the clinical cost-effectiveness of temporarily quadrupling the dose of inhaled steroid to prevent asthma exacerbations - Skeggs, Andrew; McKeever, Tricia M.; Duley, Lelia; Mitchell, Eleanor; Bradshaw, Lucy; Mortimer, Kevin; Walker, Samantha; Parrott, Steve; Wilson, Andrew; Pavord, Ian; Brightling, Chris; Thomas, Mike; et al. (BioMed Central, 2016)
BACKGROUND: Asthma is one of the commonest chronic diseases in the UK. Acute exacerbations of asthma are unpredictable, disruptive and frightening. They cause considerable morbidity and account for a large component of the health service costs of asthma. The widespread use of an asthma self-management plan, designed to encourage disease monitoring and timely intervention, can reduce exacerbations and is, therefore, recommended for all patients with asthma. Unfortunately, the majority of patients are not provided with such a plan. There are a variety of reasons for this but uncertainty about what to include in the plan when asthma control is deteriorating, but before the need for orally administered corticosteroids, is a contributing factor. The aim of this trial is to determine whether an asthma self-management plan, which includes a temporary quadrupling of the dose of inhaled corticosteroid when asthma control starts to deteriorate, reduces asthma exacerbations requiring orally administered corticosteroids or unscheduled health care consultation for asthma.